Agrivoltaics: Integration of Reused PV Modules - María-Beatriz Nieto-Morone; Miguel-Ángel Muñoz-García; David Pérez López; Carlota Bernal-Basurco; Félix García Rosillo; María del Carmen Alonso-García (Agronomy)
This study evaluates the integration of reused PV modules within an agrivoltaic system designed for sustainable horticultural production, focusing on energy performance and agricultural outcomes. The experimental setup included both new and partially repaired PV modules, installed over tomato crops under real operating conditions. The results demonstrate that reused PV modules exhibit a strong and consistent energy performance, achieving correlations between irradiance and energy output comparable to new panels. Despite slightly lower performance ratios, reused modules maintained stable efficiency and operational viability, emphasizing their potential for sustainable applications. On the agricultural side, shading provided by PV panels protects the crop yield. This study highlights the environmental and economic advantages of incorporating reused PV modules into agrivoltaic systems, including reductions in raw material extraction, electronic waste generation, and overall environmental impact. By leveraging the circular economy principles, agrivoltaics with reused PV modules provide a sustainable pathway to balance energy production and food security while optimizing land use efficiency. These findings establish the potential of agrivoltaics as a key technology in advancing the sustainable energy transition.